2016
DOI: 10.7326/m15-3118
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Chronic Severe Functional Constipation

Abstract: Ministry of Science and Technology of the People's Republic of China through the Twelfth Five-Year National Science and Technology Pillar Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
175
2
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(195 citation statements)
references
References 32 publications
6
175
2
6
Order By: Relevance
“…The lack of a sham acupuncture control makes it impossible to test whether the treatment effect of acupuncture is specific and how much is the magnitude of the treatment effect. Several trials and systematic reviews of acupuncture for irritable bowel syndrome, pain conditions, and hot flashes after chemotherapy or radiotherapy showed that the effect of acupuncture is mainly placebo effect; however, other trials of acupuncture for CFC and functional dyspepsia showed specific but small magnitude treatment effect of acupuncture . In summary, future trials should have both positive and sham control in one trial to settle the problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of a sham acupuncture control makes it impossible to test whether the treatment effect of acupuncture is specific and how much is the magnitude of the treatment effect. Several trials and systematic reviews of acupuncture for irritable bowel syndrome, pain conditions, and hot flashes after chemotherapy or radiotherapy showed that the effect of acupuncture is mainly placebo effect; however, other trials of acupuncture for CFC and functional dyspepsia showed specific but small magnitude treatment effect of acupuncture . In summary, future trials should have both positive and sham control in one trial to settle the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials and systematic reviews of acupuncture for irritable bowel syndrome, 13,18,20,23,37 pain conditions, 24,38 and hot flashes after chemotherapy or radiotherapy 39,40 showed that the effect of acupuncture is mainly placebo effect; however, other trials of acupuncture for CFC and functional dyspepsia showed specific but small magnitude treatment effect of acupuncture. 41 In summary, future trials should have both positive and sham control in one trial to settle the problem. Thirdly, we used a pragmatic design in this study, so the diet and lifestyle were not strictly controlled during the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Promising results have been reported on the EA treatment for chronic functional constipation. In a multi‐center placebo‐controlled study involving 1075 patients with severe functional constipation, 8 weeks of EA (4 times/wk) significantly increased the weekly complete spontaneous bowel movement in comparison with sham‐EA . In the article appeared in this issue, EA was found to be as effective as the prokinetic agent in reducing constipation symptoms during the treatment period but more effective than the prokinetic agent in the follow‐up period.…”
Section: Ea and Tea Treatments For Gut Dysmotilitymentioning
confidence: 96%
“…5 Another study of 1075 patients with refractory constipation showed that electroacupuncture, in which an electric current is applied to acupuncture needles inserted into the body, was effective for treatment. 6 The researchers noted that in previous studies on the effects of acupuncture, relatively intense stimulation was applied by inserting acupuncture needles (filiform needles) deep into the tissue up to the muscles. 6 Acupuncture is only performed by physicians and acupuncturists.…”
Section: Introduction Bmentioning
confidence: 99%
“…6 The researchers noted that in previous studies on the effects of acupuncture, relatively intense stimulation was applied by inserting acupuncture needles (filiform needles) deep into the tissue up to the muscles. 6 Acupuncture is only performed by physicians and acupuncturists. As acupuncture needles are inserted into the body, some patients show reluctance because of issues, such as pain, safety, and hygiene.…”
Section: Introduction Bmentioning
confidence: 99%